Pogue's war : diaries of a WWII combat historian - Pogue, Forrest C. (University Press of Kentucky, 2001)
"With a foreword by Stephen Ambrose and a preface by Franklin D. Anderson Forrest Pogue (1912-1996) was undoubtedly one of the greatest World War II combat historians. Born and educated in Kentucky, he is perhaps best known for his definitive four-volume biography of General George C. Marshall. But, as Pogue's War makes clear, he was also a pioneer in the development of oral history in the twentieth century, as well as an impressive interviewer with an ability to relate to people at all levels, from the private in the trenches to the general carrying four stars. Pogue's War is drawn from Forr
Includes index.
Keywords: Pogue, Forrest C. -- Diaries.; Pogue, Forrest C.; Military historians -- United States -- Diaries.; World War, 1939-1945 -- Campaigns -- Western Front.; World War, 1939-1945 -- Personal narratives, American.; Guerre mondiale, 1939-1945 -- Campagnes et batailles -- Front occidental.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY -- Military -- World War II.; HISTORY -- Military -- Veterans.; Military campaigns; Military historians; United States; Western Front (World War (1939-1945)); Tweede Wereldoorlog.; Krijgsgeschiedenis (wetenschap); Guerre mondiale (1939-1945) -- Campagnes et batailles -- Front occidental -- Récits personnels américains.; Soldat; Weltkrieg -- 1939-1945; Erlebnisbericht; USA; 1939 - 1945; diaries.; autobiographies (literary works); Personal narratives; Autobiographies; Diaries; Personal narratives -- American; Autobiographies.; Diaries.; Personal narratives.; Journaux intimes.; Récits personnels.